ANALISIS KEMAMPUAN BERPIKIR KRITIS SISWA KELAS V DI MIS ALWASHLIYAH TERHADAP KONSEP BANGUN RUANG - Anim Anim; Eliza Dwi Ananda; Andini Andini; Ghea Marsha; Dahrina Azmi Asyarti; Sondang Purnamasari Pakpahan (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2026)
Abstract: This study aims to analyze the critical thinking abilities of fifth-grade students at MIS Alwashliyah Tanjung Balai on three-dimensional shapes concepts. Using qualitative descriptive method, data were collected from 18 students through observation, interviews, and post-learning tests based on three indicators: interpretation, analysis, and inference. Results showed students' critical thinking abilities were at moderate level, with only 16.67% achieving full mastery. Main difficulties were in analysis and inference indicators, manifested in identifying shape properties and drawing valid conclusions. Students frequently confused cube and cuboid characteristics and failed in contextual calculations. These weaknesses stem from poor spatial visualization and limited understanding of abstract concepts. The study recommends implementing concrete media-based learning methods to optimize critical thinking development in spatial geometry learning. Keyword: critical thinking; three-dimensional shapes; elementary mathematics; concrete media; spatial visualization. Abstrak: Penelitian ini bertujuan menganalisis kemampuan berpikir kritis siswa kelas V MIS Alwashliyah Tanjung Balai pada materi bangun ruang. Menggunakan metode deskriptif kualitatif, data dikumpulkan dari 18 siswa melalui observasi, wawancara, dan tes pasca pembelajaran berdasarkan tiga indikator: interpretasi, analisis, dan inferensi. Hasil menunjukkan kemampuan berpikir kritis siswa berada pada kategori sedang, dengan hanya 16,67% siswa mencapai penguasaan penuh. Kesulitan utama pada indikator analisis dan inferensi, termanifestasi dalam mengidentifikasi sifat bangun ruang dan menarik kesimpulan valid. Siswa sering keliru membedakan kubus dan balok serta gagal dalam perhitungan kontekstual. Kelemahan ini bersumber dari visualisasi spasial rendah dan pemahaman konsep abstrak terbatas. Penelitian merekomendasikan implementasi metode pembelajaran berbasis media konkret untuk mengoptimalkan kemampuan berpikir kritis dalam pembelajaran geometri ruang. Kata kunci: berpikir kritis; bangun ruang; matematika SD; media konkret; visualisasi spasial